Desenvolvimento de algoritmo e programa de análise de estruturas em concreto armado levando em consideração as etapas construtivas e a variação das características do concreto com o tempo - Oliveira, Marcelo Eduardo Fernandes de (2019)
The structural analysis of reinforced concrete buildings fabricated on site is usually done considering the structure in its final state, with the load applied on a given date and the concrete with its characteristic values. To examine a structural analysis closer to reality, it is necessary to consider the evolutionary stages of the building construction, the dates in which the various actions begin to act, the actual values of the resistance, the modulus of elasticity and the current structure geometry at the time. This work aims to elaborate a detailed procedure that takes all the mentioned aspects in consideration, including the provisional stages of shoring, without using simplified techniques currently found in literature. Certain structural analysis programs may consider some of the variables listed, but they must be configured through a laborious and repetitive process, and end up making the analysis slow, often incomplete and error-prone, due to the difficulty of data entry. With modern database programming techniques, we have elaborated an algorithm that analyzes the structure of the building considering the presented variables, developing a three-dimensional frames program specially tailored to suit the algorithm presented in this work. Thus, the behavior and the displacement of the structure throughout its construction and use can be visualized, enabling a better choice for the cross sections of beams, columns and slabs.